SOC 2016 - Witt, John (McGraw Hill, 2016)
A tool that develops students' sociological imaginations by placing them in provocative scenarios where they must analyze various sources and determine a solution. With McGraw-Hill's digital tools, it helps you to focus on what you do best-teaching.